Continuous combined therapy with low doses in women in early postmenopausal period - Sobczuk, Anna; Nadel, Iwona; Pertyński, Tomasz (Menopause Review/Przegląd Menopauzalny, 2002)
Aim of study: Evaluation of efficacy of therapy with estrogen and gestagen in lower doses (Activelle), its tolerance and side effects prevalence in women in early postmenopausal period, using previously combined or cyclic regimens with higher doses. Material and methods: 118 women were included into study, 112 of them have finished treatment. The mean age of studied patients was 53,1 years. The mean age of menopause in study group was 49,2±2,28 years. For treatment efficacy evaluation we used Green climacteric symptoms scale. Results: We observed similar level of climacteric symptoms during either sequential or continuous combined therapy with lower estradiol doses (Activelle). Activelle was well tolerated and revealed the same efficacy in treatment of menopausal complains as previously used sequential therapy with higher doses of estrogens. After three months of continuous therapy we noted lower incidence of side effects and bleeding, mood improvement, decreased restlessness and anxiety and increased self-acceptance in treated women.